The Impact of Polypharmacy on the Effectiveness and Safety of Non-vitamin K Antagonist Oral Anticoagulants in Patients with Atrial Fibrillation - Grymonprez, Maxim; Petrovic, Mirko; De Backer, Tine L.; Steurbaut, Stephane; Lahousse, Lies (Thrombosis and Haemostasis, 2023)
Background Polypharmacy may affect outcomes in patients with atrial fibrillation (AF) using non-vitamin K antagonist oral anticoagulants (NOACs) or vitamin K antagonists (VKAs) due to interactions or reduced adherence, but comparative data are lacking. Therefore, the impact of polypharmacy on AF-related outcomes and benefit–risk profiles of NOACs in patients with polypharmacy were investigated.Methods AF patients initiating anticoagulation between 2013 and 2019 were included using Belgian nationwide data. Inverse probability of treatment weighted Cox regression was used to investigate outcomes.Results Among 254,478 AF patients, 167,847 (66.0%) used ≥5 drugs. Polypharmacy was associated with higher stroke or systemic embolism (stroke/SE) (adjusted hazard ratio [aHR]: 1.08, 95% confidence interval [CI]: 1.02–1.15), all-cause mortality (aHR: 1.45, 95% CI: 1.40–1.50), and major bleeding risks (aHR: 1.29, 95% CI: 1.23–1.35). Among patients with polypharmacy, NOACs were associated with lower stroke/SE (aHR: 0.68, 95% CI: 0.63–0.73), all-cause mortality (aHR: 0.80, 95% CI: 0.77–0.84), major bleeding (aHR: 0.92, 95% CI: 0.87–0.97), and intracranial bleeding risks (aHR: 0.77, 95% CI: 0.69–0.85), but higher gastrointestinal bleeding risks (aHR: 1.10, 95% CI: 1.01–1.19) compared to VKAs. Major bleeding risks were lower with apixaban (aHR: 0.79, 95% CI: 0.74–0.85), but nonsignificantly different with other NOACs compared to VKAs. Lower major bleeding risks were observed with dabigatran (aHR: 0.91, 95% CI: 0.85–0.97) and apixaban (aHR: 0.77, 95% CI: 0.73–0.81) compared to rivaroxaban, and with apixaban compared to dabigatran (HR: 0.83, 95% CI: 0.77–0.90) and edoxaban (HR: 0.77, 95% CI: 0.70–0.85).Conclusion Polypharmacy was associated with increased thromboembolic, bleeding, and mortality risks in AF patients. NOACs had better benefit–risk profiles than VKAs in patients with polypharmacy.
Keywords: atrial fibrillation; polypharmacy; NOAC; thromboembolism